Efektifitas Penggunaan sarana Sanitasi Berbasis Masyarakat (SANIMAS) dengan perubahan Perilaku hidup bersih dan sehatdi Desa Errabu Kecamatan Bluto Kabupaten Sumenep 2017 - Laylatul Hasanah (Wiraraja Medika : Jurnal Kesehatan, 2018)
Introduction : Broadly, definition of sanitation includes management, human waste, solidwaste and drainage. Sanitation is one significant challenge for government to reduce poverty inIndonesia. Community based sanitation program is a program launched by government toemphasize clean and healthy lifestyle for community. Sumenep regency is one of the regenciesreceived the benefits of this Community based sanitation program that implemented through theconstruction of MCK plus in Errabu village.Methods :This research is descriptive study using purposive sampling. Number of samplesin this study are 10 communities, those are1 chief of non-governmental group, 1 secretary of nongovernmental group, 1 treasurer of non-governmental group, and 7 community users ofcommunity based sanitation facilities. Technique of collecting data uses an in-depth interview.Results : The community users of community based sanitation facilities are only 20 familiesor 23% of the targeted population which is 115 families. It is related to the behavior of thecommunity that has not changed.Conclusion : Efforts to change the behavior of the community can be done by providingknowledge and education through extension methods about clean and healthy life behavior.